STUDY OF KOJIC ACID PRODUCTION IN ENDOPHYTIC FUNGI AND APPLICATION IN DECAY PREVENTION TOMATO (Lycopersicum Esculentum L.) - Ola, Antonius R.B.; Kadang, Luther; Bagung, Dionisius Yosama (Universitas Nusa Cendana, 2024)
A study of kojic acid production in the endophytic fungi Aspergillus flavus was conducted to identify the effect of kojic acid on efforts to prevent decay and manage the quality of shelf life of tomato fruit (Lycopersicum esculentum L.). The kojic acid obtained showed good results in preventing tomato fruit spoilage. The organoleptic test results on the texture and aroma of tomato rot stated the highest favorability in the test treatment with kojic acid, namely in the treatment of tomato fruit stored by spraying 1% kojic acid. The ability of kojic acid to extend the shelf life of tomato fruit is seen from its antibacterial activity and is able to suppress the rate of respiration and transpiration in tomato fruit.